Servant Leadership and its Impact on the Effectiveness of Teamwork - Hassan, Zainab Amer; Raheemah, Salma Hatyta (Journal of Economics and Administrative Sciences, 2021)
The research problem stems from the suffering of organizations from the weakness of their organizing aspect and the weak influence of the leadership on the subordinates and their dispersion. Organizations today are in rapid development and therefore work relations are not dominated by the humanitarian aspect and the first goal has become productivity. The research aims to identify the influence of servant leadership and its dimensions as an independent variable on the effectiveness of work teams as an approved variable and their importance increases when these organizations are service organizations, and how their influence increases when this leadership is the servant leadership and its dimensions in the Health Department in Baghdad/ Al-Rusafa, and based on the importance of the research topic and the importance of the research sample and the researched organization. The researchers adopted the descriptive analytical approach which deals with 176 workers representing the research sample from 310 workers (the research community) using questionnaire as a main tool for data collection, which included 61 items. The research adopts appropriate statistical methods for the data analysis including t-test, F-test, and exploratory analysis to test its hypotheses within SPSS v.21. The most important findings are that it can proved the validity of the hypotheses which they were embodied by the impact of servant leadership, directly and indirectly, on the effectiveness of work teams at the Health Department in Baghdad/ Al-Rusafa with the most important applications of servant leadership and how to strengthen servant leadership